FORMAL CHARGE — A NOVEL METHOD FOR TEACHING THEORETICAL INORGANIC CHEMISTRY - Biswal, Bibhuti Narayan (SCHOOL SCIENCE, 2010)
All atoms within a neutral molecule need not be neutral. The location of any charge is often important for understanding reactivity of the molecule. Ions bear a positive or negative charge. If the ion is polyatomic (i.e. constructed of more than one atom), we might ask which atom (s) of ion carry the charge? Thus knowledge of charge distribution over the atoms in a molecule or ion (identification of atom that are electron rich or electron poor) can be useful to interpret many facets of organic chemistry, including how and why reactions occur (mechanisms) or how molecules interact with each other, a feature which strong.